The effect of carbon fibre stitching on the tensile behaviour of secondary bonded single- and double-lap composite joints. (1st June 2021) - Sun, C.; Jia, P.; Chen, C.; Moradi, A.; Zhou, J.; Al Teneiji, M.; Cantwell, W.J.; Guan, Z.W.
Highlights: A novel stitching technology for strengthening composite joints. Modelling the tensile behaviour of single- and double-lap stitched joints. Development of semi-empirical formulae for further parametric studies. Both numerical and theoretical models are validated against the related test results. The technology developed has potential for broad applications in composite repair. Abstract: This paper presents a novel stitching method for enhancing the mechanical properties of secondary-bonded CFRP single- and double-lap joints. In this approach, holes were drilled in the secondary bonded joints and carbon fibre threads were stitched through the joints. The vacuum resin infusion technique was then used to integrate the threads with the joints. The tensile properties of the stitched joints were measured and compared with those offered by traditional bonded (unstitched) joints in order to investigate the potential of the stitching method. The experimental results show that by using this stitching method, the ultimate tensile strength of the stitched single- and double-lap joints are respectively 200% and 130% greater than the corresponding conventional bonded joints. A three-dimensional finite element analysis (FEA) has been undertaken to predict the mechanical response of the stitched joints. The numerical analysis showed that the stiffness degradation at the end of overlap area is held back by the stitching fibres. Finally, the semi-empirical formulae has been developed to investigate the effect of hole pattern and thread size on the joint behaviour. Both the numerical and theoretical predictions are validated against the corresponding experimental results with good correlation.